Final report on SIM.AUV.A-K1 : LS1P microphone interlaboratory comparison - Wong, G. (2007)
The final results of Sistema Interamericano de Metrologia (SIM) interlaboratory comparison on microphone calibration SIM.AUV.A-K1 in the frequency range from 125 Hz to 8000 Hz are presented. Initially the comparison involved NORAMET countries: USA, Canada and Mexico. Later, the comparison was extended to include Argentina and Brazil, resulting in a SIM.AUV.A-K1 microphone interlaboratory comparison. The national metrology institutes (NMIs) of the five American countries that participated were the Institute for National Measurement Standards (INMS–Canada), National Institute of Standards and Technology (NIST–USA), Centro Nacional de Metrología (CENAM–Mexico), Instituto Nacional de Metrologia, Normalização e Qualidade Industrial (INMETRO–Brazil) and Instituto Nacional de Tecnología Industrial (INTI–Argentina). The INMS, Canada was the pilot laboratory that provided the data for this report. The final results were presented, discussed and agreed upon by all participants during a meeting held in INMETRO in October 2000. The maximum RMS deviation for the two LS1P laboratory standard microphones measured by the above participants is 0.037 dB.